Do the Benefits of Educational Attainment for Late-life Cognition Differ by Racial/Ethnic Group?: Evidence for Heterogenous Treatment Effects in the Kaiser Healthy Aging and Diverse Life Experience (KHANDLE) Study - Eng, Chloe W; Glymour, Medellena Maria; Gilsanz, Paola; Mungas, Dan M; Mayeda, Elizabeth R; Meyer, Oanh L; Whitmer, Rachel A (Alzheimer disease and associated disorders, 2021)
Educational attainment is associated with late-life cognitive performance and dementia; few studies have examined diverse racial/ethnic groups to assess whether the association differs by race/ethnicity. We investigated whether the association between educational attainment and cognition differed between White, Black, Asian, and Latino participants in the Kaiser Healthy Aging and Diverse Life Experiences study (n=1348). Covariate-adjusted multivariable linear regression models examined domains of verbal episodic memory, semantic memory, and executive functioning. We observed significant effect heterogeneity by race/ethnicity only for verbal episodic memory (P=0.0198), for which any schooling between high school and college was beneficial for White, Asian, and Black participants, but not Latino participants. We found no evidence of heterogeneity for semantic memory or executive function. With the exception of Latino performance on verbal episodic memory, more education consistently predicted better cognitive scores to a similar extent across racial/ethnic groups, despite likely heterogenous educational and social experiences.